Thickness effects of base wall and inlet pipe on the structural integrity of reactor pressure vessels considering ductile-to-brittle transition. (November 2019) - Sun, Xin; Yao, Jian; Chai, Guozhong; Bao, Yumei
Abstract: During pressurized thermal shock (PTS) transient, the surface crack near the inlet nozzle region of a reactor pressure vessel (RPV) may propagate constantly and even through the thickness of base wall. The temperature dependent material properties are introduced to evaluate the thickness effects of base wall and inlet pipe on the integrity of the structure. By means of elastic and elastic-plastic fracture analysis, the different ultimate internal pressure values related to nil-ductility reference temperature for various base wall thicknesses are compared. It is confirmed that the elastic-plastic fracture analysis is more applicable for relatively low nil-ductility reference temperatures. It is also found that the results obtained by the XFEM are in good agreement with those obtained by the traditional K-T method in case of brittle initiation. Then the thickness effects of inlet pipe on the structural integrity are emphatically analyzed. Also, the effect of crack sizes on the bearing capacity of the nozzle region is demonstrated by crack propagation paths and damage degrees. To avoid brittle fracture, the allowable inlet pipe thicknesses corresponding to various crack sizes in a wide range of reference temperatures are obtained. The proposed method has a good ability to predict the integrity of the RPV structure through the analysis, comparison and mutual verification of different finite element meshes. Highlights: A 3-D finite element model is established for the beltline around the inlet nozzles of reactor pressure vessels. The XFEM are used to simulate the crack propagation for different thicknesses of base wall and inlet pipe under pressurized thermal shock. By comparing the results of elastic and elastic-plastic fracture analysis, the law of ductile-brittle transition is summarized.